STRATEGI PEMERINTAH THAILAND DALAM MEMPERBAIKI KETIMPANGAN EKONOMI: STUDI LITERATUR - Marcella, Tasya Fara; Dwi Saraswati, Nabila (Universitas Cenderawasih, 2024)
This study aims to understand the economic inequality that exists in Thailand and evaluate the various strategies that have been undertaken by the government to address it. Economic inequality in the country reflects an imbalance in the distribution of income and wealth that creates stark differences between groups of people. This problem has worsened due to the impact of the Covid-19 pandemic, which has caused a significant decline in Gross Domestic Product (GDP) growth and rising unemployment. This issue is considered crucial because prolonged inequality can hinder the achievement of inclusive economic growth and threaten social stability in Thailand. The research uses a descriptive qualitative method with a literature study approach, relying on secondary data from various official reports, scientific articles, and journals. The results show that the Thai government has adopted several strategies, such as the development of a universal health system, the provision of scholarships to increase access to education, and sustainable environmental management. The study recommends that the government pay more attention to rural areas that are often neglected, and conduct regular evaluations of the effectiveness of these programs to ensure their sustainability in reducing economic inequality.